Altitude training for sea level performance: Best practices and timing for championships 2011 IAAF Athletics Championships Daegu, South Korea - Chapman, R.; Wilber, R. (2011)
The 2011 IAAF Outdoor Track & Field Championships will be held in Daegu, South Korea from August 26 to September 4. Between the end of the USA Championships and the start of the World Championships there are 62 days, allowing distance athletes (who so desire) adequate time to complete an altitude training camp. Below is information regarding potential impact, the latest scientific information on best practices for executing an altitude training camp, and current knowledge on appropriate timing of the camp relative to the date of championship competition.